(untitled) (American Journal of Interdisciplinary Research and Development, 2025)
The article "Parameterization of Translation Strategy" explores the systematic approach to translation by identifying and analyzing key parameters that influence strategic choices. It emphasizes the importance of linguistic, cultural, and contextual factors in the translation process. The study offers a structured framework for categorizing translation strategies based on text type, audience, and purpose. By examining different translation scenarios, the article contributes to a deeper understanding of how translators make decisions. This research is valuable for both professional translators and scholars aiming to enhance translation quality and efficiency.